Viral Apoptosis Evasion via the MAPK Pathway by Use of a Host Long Noncoding RNA - Barichievy, Samantha; Naidoo, Jerolen; Boullé, Mikaël; Scholefield, Janine; Parihar, Suraj P.; Coussens, Anna K.; Brombacher, Frank; Sigal, Alex; Mhlanga, Musa M. (Frontiers in Cellular and Infection Microbiology, 2018)
An emerging realisation of infectious disease is that pathogens can cause a high incidence of genetic instability within the host as a result of infection-induced DNA lesions. These often lead to classical hallmarks of cancer, one of which is the ability to evade apoptosis despite the presence of numerous genetic mutations that should be otherwise lethal. The Human Immunodeficiency Virus type 1 (HIV-1) is one such pathogen as it induces apoptosis in CD4+ T cells but is largely non-cytopathic in macrophages. As a consequence there is long-term dissemination of the pathogen specifically by these infected yet surviving host cells. Apoptosis is triggered by double-strand breaks (DSBs), such as those induced by integrating retroviruses like HIV-1, and is coordinated by the p53-regulated long noncoding RNA lincRNA-p21. As is typical for a long noncoding RNA, lincRNA-p21 mediates its activities in a complex with one of its two protein binding partners, namely HuR and hnRNP-K. In this work, we monitor the cellular response to infection to determine how HIV-1 induces DSBs in macrophages yet evades apoptosis in these cells. We show that the virus does so by securing the pro-survival MAP2K1/ERK2 cascade early upon entry, in a gp120-dependent manner, to orchestrate a complex dysregulation of lincRNA-p21. By sequestering the lincRNA-p21 partner HuR in the nucleus, HIV-1 enables lincRNA-p21 degradation. Simultaneously, the virus permits transcription of pro-survival genes by sequestering lincRNA-p21’s other protein partner hnRNP-K in the cytoplasm via the MAP2K1/ERK2 pathway. Of particular note, this MAP2K1/ERK2 pro-survival cascade is switched off during T cell maturation and is thus unavailable for similar viral manipulation in mature CD4+ T cells. We show that the introduction of MAP2K1, ERK2 or HDM2 inhibitors in HIV-infected macrophages results in apoptosis, providing strong evidence that the viral-mediated apoptotic block can be released, specifically by restoring the nuclear interaction of lincRNA-p21 and its apoptosis protein partner hnRNP-K. Together, these results reveal a unique example of pathogenic control over mammalian apoptosis and DNA damage via a host long noncoding RNA, and present MAP2K1/ERK2 inhibitors as a novel therapeutic intervention strategy for HIV-1 infection in macrophages.